The Effect of Information Technology on Product Innovation and Business Sustainability as A Mediation of Blue Marketing Strategy in Processed Fish Products in Bengkalis Regency - Kurniatul Fil Khoirin (CV. Civiliza Publishing, 2026)
This study investigates the effect of information technology on product innovation and business sustainability, with blue marketing strategy serving as a mediating variable among processed fish product SMEs in Bengkalis Regency, Indonesia. This research addresses the limited empirical evidence on sustainability-oriented marketing as a strategic mechanism linking digital transformation to long-term business performance in coastal-based SMEs. A quantitative approach was employed using a survey method, with data collected from 311 processed fish SMEs through structured questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables. The results indicate that information technology has a strong and significant positive effect on product innovation and business sustainability. Information technology also significantly enhances the adoption of blue marketing strategies. Furthermore, blue marketing strategy positively influences product innovation and business sustainability and partially mediates the relationship between information technology and both outcome variables. The structural model demonstrates substantial explanatory power, with R² values of 0.549 for product innovation, 0.481 for business sustainability, and 0.412 for blue marketing strategy. All constructs satisfy reliability and convergent validity criteria, and no multicollinearity issues are detected. Theoretically, this study extends the digital innovation and sustainability literature by positioning blue marketing as a strategic mediator in SME development. Practically, the findings provide policy-relevant insights for SMEs and local governments in promoting technology-driven and environmentally sustainable business strategies within the fisheries sector.